2019
DOI: 10.1016/j.bpj.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Studies of an RNA Duplex Electrostatics by Ion Counting

Abstract: RNAs are one of the most charged polyelectrolytes in nature, and understanding their electrostatics is fundamental to their structure and biological functions. An effective way to characterize the electrostatic field generated by nucleic acids is to quantify interactions between nucleic acids and ions that surround the molecules. These ions form a loosely associated cloud referred to as an ion atmosphere. Although theoretical and computational studies can describe the ion atmosphere around RNAs, benchmarks are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 82 publications
(163 reference statements)
5
53
0
Order By: Relevance
“…As a result, c (ρ) shows only a single dominant peak around the major groove. The magnitude of the peak reflects the strength of attractive forces between positively charged cations and negatively charged RNA surface and reveals a stronger electrostatic potential for dsRNA than for dsDNA, supporting results of recent ion-counting experiments ( 42 ). The 3D ion density profiles visually highlight the ion-binding preferential locations ( Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As a result, c (ρ) shows only a single dominant peak around the major groove. The magnitude of the peak reflects the strength of attractive forces between positively charged cations and negatively charged RNA surface and reveals a stronger electrostatic potential for dsRNA than for dsDNA, supporting results of recent ion-counting experiments ( 42 ). The 3D ion density profiles visually highlight the ion-binding preferential locations ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…Past studies on DNA show the importance of this type of information in deciphering the sequence variability of dsNA molecules, an area that needs further development (35). However, a promising line of study integrates experimental and computational approaches to study RNA conformations (36)(37)(38)(39)(40)(41)(42)(43). Simulations provide atomic-level spatial resolution for macromolecular structure and dynamics while closely correlated experiments can be used to finely tune the simulation parameters (36,38,44) or guide the efficient exploration of conformational space sampled (37,40,43).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to nucleic acids, the proteins appear to have a weaker ability to accumulate counterions per charge. Whereas Δ N ia (cations)/| n | is 0.80–0.90 for DNA and RNA duplexes at ionic strength < 100 mM ( 8 , 12 ), our NMR data show that Δ N ia (anions)/| n | is 0.56 for the Antp homeodomain and 0.68 for BPTI. The weaker ability to attract counterions is presumably due to the smaller charge density on the molecular surfaces.…”
Section: Resultsmentioning
confidence: 60%
“…For nucleic acids, Δ N ia (anions) and Δ N ia (cations) have been well studied. Herschlag and coworkers studied the ion atmosphere around various DNA and RNA molecules using ion-counting methods ( 7 , 8 , 12 ). They showed that the experimental Δ N ia (anions) and Δ N ia (cations) data agreed well with those predicted by the Poisson–Boltzmann equation-based theory.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the introduction, it has been suggested that the Poisson-Boltzmann theory may inaccurately predict electrostatic potentials for highly charged systems (12). Previous studies showed that the Poisson-Boltzmann equation-based approaches can accurately predict the total number of ions accumulated around highly charged proteins (32) and nucleic acids (33)(34)(35). However, the total number of accumulated ions is more relevant to long-range electrostatic potentials.…”
Section: Comparison With the Poisson-boltzmann Equation-based Electrostaticmentioning
confidence: 99%